2006
DOI: 10.1038/sj.onc.1209386
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation of the Wnt antagonist SFRP1 in breast cancer is associated with unfavourable prognosis

Abstract: The canonical Wnt signalling pathway plays a key role during embryogenesis and defects in this pathway have been implicated in the pathogenesis of various types of tumours, including breast cancer. The gene for secreted frizzled-related protein 1 (SFRP1) encodes a soluble Wnt antagonist and is located in a chromosomal region (8p22-p12) that is often deleted in breast cancer. In colon, lung, bladder and ovarian cancer SFRP1 expression is frequently inactivated by promoter methylation. We have previously shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
210
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 236 publications
(230 citation statements)
references
References 39 publications
(46 reference statements)
16
210
1
3
Order By: Relevance
“…In primary breast tumours, methylation frequencies of SFRP1, SFRP2, SFRP5 and DKK1 were 40, 77, 71 and 19%, respectively. Although the frequency of SFRP1 methylation in our samples was somewhat lower than those reported by Lo et al (2006) and Veeck et al (2006), we also found that a substantial number of breast tumours harbour SFRP1 methylation. In addition, we found that SFRP2 and SFRP5 are methylated in both cultured breast cancer cells and primary breast cancers at quite high frequencies.…”
contrasting
confidence: 90%
See 1 more Smart Citation
“…In primary breast tumours, methylation frequencies of SFRP1, SFRP2, SFRP5 and DKK1 were 40, 77, 71 and 19%, respectively. Although the frequency of SFRP1 methylation in our samples was somewhat lower than those reported by Lo et al (2006) and Veeck et al (2006), we also found that a substantial number of breast tumours harbour SFRP1 methylation. In addition, we found that SFRP2 and SFRP5 are methylated in both cultured breast cancer cells and primary breast cancers at quite high frequencies.…”
contrasting
confidence: 90%
“…Using immunohistochemical analysis, Klopocki et al (2004) found that expression of SFRP1 protein was absent in 46% of invasive breast tumours and in 43% of carcinoma in situ. In addition, two groups recently reported frequent SFRP1 methylation in primary breast tumours (Lo et al, 2006;Veeck et al, 2006), and Bafico et al (2004) clearly demonstrated a novel autocrine mechanism leading to constitutive Wnt signalling in breast cancer, which could be suppressed by SFRP1 and DKK1. Taken together, these results suggest that loss of SFRP1 function is a key mechanism by which Wnt signalling is activated in breast cancer.…”
mentioning
confidence: 97%
“…HeLa/HtTA8/8 cells stably expressing MIF under control of a Tet-off cassette were cultured and induced as described (Nguyen et al, 2003). The normal mammary epithelial cell line MCF-12A and the breast carcinoma cell lines MCF-7 (infiltrating ductal adenocarcinoma), MDA-MB-468 (infiltrating adenocarcinoma) and ZR-75-1 (infiltrating ductal carcinoma) were obtained from the Dahl lab (source ATCC) and were cultured as described previously (Veeck et al, 2006). Briefly, MCF-12A cells were cultured in MDEM medium containing 10% FCS and were additionally supplemented with 10 mg/ml insulin, 500 ng/ml hydrocortisone and 20 ng/ml epidermal growth factor (SigmaAldrich, Munich, Germany).…”
Section: Cell Culturementioning
confidence: 99%
“…Interestingly, sFRP1 functions as a negative regulator of the Wnt pathway and blocks the activation of the downstream target genes (Kawano and Kypta, 2003). Downregulation of the sFRP1 has been found in a variety of malignancies including colon (Caldwell et al, 2004), breast (Veeck et al, 2006), bladder (Stoehr et al, 2004), ovarian (Takada et al, 2004), and lung (Fukui et al, 2005) cancers. It has been reported that reconstitution of sFRP1 inhibits HCC growth in vitro and in vivo, and the sFRP1 restoration offers a potential therapeutic approach for treatment of HCC (Hu et al, 2009;Jiang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in the sFRP1 expression due to promoter hypermethylation may result in the activation of the Wnt pathway and consequent tumor development. Interestingly, reduced expression of sFRP1 has been found in many malignancies, including colorectal (Caldwell et al, 2004;Suzuki et al, 2004), lung (Fukui et al, 2005), ovarian (Takada et al, 2004), breast (Veeck et al, 2006), esophageal (Zou et al, 2005;Clement et al, 2006), and liver (Shih et al, 2006) cancers.…”
mentioning
confidence: 99%